Odpowiedź :
Rozwiązanie układu równań
{x + 6y = 15
{2x + 3y = 12
{x = 15 - 6y
{2(15 - 6y) + 3y = 12
{x = 15 - 6y
{30 - 12y + 3y = 12 / - 30
{x = 15 - 6y
{-9y = -18 / : (-9)
{y = 2
{x = 15 - 6 · 2
{y = 2
{x = 15 - 12
{x = 3
{y = 2
Sprawdzenie rozwiązania
L = 3 + 6 · 2 = 3 + 12 = 15
P = 15
L = P
L = 2 · 3 + 3 · 2 = 6 + 6 = 12
P = 12
L = P
Odpowiedź:
Szczegółowe wyjaśnienie:
{x + 6y = 15
{2x + 3y = 12
{ x = 15 - 6y
{ 2 * (15 - 6y ) + 3y = 12
{ 30 - 12y + 3y = 12
30 - 9y = 12
- 9y = 12 - 30
-9y = - 18 /:(-9)
y = 2
{ x = 15 - 6y
x = 15 - 6 * 2
x = 15 - 12
x = 3
{ x = 3
{ y = 2
Spr:
Pierwsze równanie:
{x + 6y = 15
L = 3 + 6 * 2 = 3 + 12 = 15
P = 15
L = P
Drugie równanie:
{2x + 3y = 12
L = 2 * 3 + 3 * 2 = 6 + 6 = 12
P = 12
L = P